Introduction - Matos, F.; Valter Vairinhos; Paulo Mauricio Selig; Edvinsson, L. (Intellectual capital management as a driver of sustainability: Perspectives for organizations and society, 2019)
The economic, social and environmental pressures challenge the organizations, cities, regions and even countries for the need to undertake efforts to achieve sustainable development. The decision-making processes in a digital economy implies balancing economic, environmental and social aspects, in order to achieve excellence towards a transparent and inclusive governance.